Prevalence of exclusive breastfeeding in Indonesia: a qualitative and quantitative study - Elizabeth Yohmi; Nanis Sacharina Marzuki; Eveline Nainggolan; I Gusti Ayu Nyoman Partiwi; Badriul Hegar Sjarif; Hanifah Oswari (Indonesian Pediatric Society, 2015)
Background Breast milk is the best and most ideal food for babies because it contains all nutrition needed for their optimal growth and development. Babies who receive breast milk will have strong immune system, good brain development, and closer emotional bonding with their mothers. Considering the importance of breast milk, Indonesian government has been campaigning to endorse exclusive breastfeeding up to six months in the last four years. To date, there is no national data available to evaluate the exclusive breastfeeding program. Therefore, Indonesian Pediatric Society (IDAI) conducted a national survey on breastfeeding to investigate exclusive breastfeeding rate in Indonesia. Objective To find out the prevalence of exclusive breastfeeding in Indonesia. Methods This study included 22 provinces in Indonesia and targeted on mothers with infants aged 0-11 months. For the quantitative portion of the study we used simple random sampling design to get the prevalence from the population. For the qualitative interview data we used a stratified random sampling design to ensure that each infant age group was well represented. Survey location in each province was selected based on defining the capital city to be urban area and its sub-urban areas to be rural. This study was performed between October – November 2010. Results We found that the prevalences of breastfeeding among baby 0-11 months was quite high which were 91%, 86%, and 72% in infants aged 0-3 months, 0-6 months, and 6-11 months, respectively. Interestingly, the prevalence of breastfeeding in urban area was higher than in rural area for infants aged 6-11 months. However, despite the high prevalence of giving breast milk, less than half of mothers gave breast milk exclusively, to babies aged 0-3 months and to those aged 0-6 months. The awareness to exclusively breastfeed was greater for urban mothers than for rural ones in those with infants aged 0-6 months. Mothers with high socioeconomic status had the highest prevalence of exclusive breastfeeding. The prevalence of breastfeeding without formula was still the highest up to 12 months but the role of giving formula was increasing especially in rural area. The prevalence of breast milk introduced as the first milk was around 60%. Java and Sumatra had lower prevalence of breast milk introduced as the first milk compared to Kalimantan and Sulawesi. We also found that mothers started giving solid food from an early age, especially in rural areas. With increasing age, the frequency of giving breast milk declined in both urban and rural areas. Conclusion The overall prevalence of exclusive breastfeeding up to 6 months of age in Indonesia was 49.8%. Maternal unemployment and high family socioeconomic status were associated with longer duration of breastfeeding.